Factors Associated to the Decision Making of Colombian Budget - Huertas, Jaime Abel; Salinas, Adriana Francisca (Sociedad y Economía, 2019)
The following paper proposes an analysis of the debates made by the members of the Economic Commissions of the Congress of Colombia on the General Government Budget from 2002 to 2009, to determine if the decisions on this have been taken with bounded rationality. The theoretical basis are the approaches to decision making made by Lindblom (1959), who assumes the concept of bounded rationality of the agents proposed by Simon (1957). The information of the sessions is analyzed through a model where debate, as a dependent variable, is explained with covariates related to the characteristics of the members of the parliament. Based on a longitudinal statistical model with informative drop-out and time-dependent covariates, the found factors associated to the debate allowed us to conclude that the decisions were not taken with any absolute technical rationality.